2021
DOI: 10.3389/fonc.2021.662273
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound in the Differential Diagnosis and Risk Stratification of ACR TI-RADS Category 4 and 5 Thyroid Nodules With Non-Hypovascular

Abstract: ObjectiveThis study aims to investigate the value of contrast-enhanced ultrasound (CEUS) in the differential diagnosis and risk stratification of ACR TI-RADS category 4 and 5 thyroid nodules with non-hypovascular.MethodsFrom January 2016 to December 2019 in our hospital, 217 ACR TI-RADS category 4 and 5 nodules with non-hypovascular in 210 consecutive patients were included for a derivation cohort. With surgery and/or fine-needle aspiration (FNA) as a reference, conventional ultrasound (US) features and CEUS f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 49 publications
1
18
0
3
Order By: Relevance
“…Prospectively, because the three investigated TIRADSs had not considered the locations of the thyroid nodules, cervical lymph nodes, epidemic factors, contrast-enhanced US features, US elastography, artificial intelligence, and so on. Some experts have suggested adding one or more of these variables to extend and augment these systems and to improve their risk stratification efficiency (14,(28)(29)(30)(31)(32). Wang, et al reported that contrast-enhanced US combining with conventional US in differentiating ACR TI-RADS category 4 and 5 nodules with non-hypovascular may improve the malignancy risk stratification of non-hypovascular thyroid nodules (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospectively, because the three investigated TIRADSs had not considered the locations of the thyroid nodules, cervical lymph nodes, epidemic factors, contrast-enhanced US features, US elastography, artificial intelligence, and so on. Some experts have suggested adding one or more of these variables to extend and augment these systems and to improve their risk stratification efficiency (14,(28)(29)(30)(31)(32). Wang, et al reported that contrast-enhanced US combining with conventional US in differentiating ACR TI-RADS category 4 and 5 nodules with non-hypovascular may improve the malignancy risk stratification of non-hypovascular thyroid nodules (28).…”
Section: Discussionmentioning
confidence: 99%
“…Some experts have suggested adding one or more of these variables to extend and augment these systems and to improve their risk stratification efficiency (14,(28)(29)(30)(31)(32). Wang, et al reported that contrast-enhanced US combining with conventional US in differentiating ACR TI-RADS category 4 and 5 nodules with non-hypovascular may improve the malignancy risk stratification of non-hypovascular thyroid nodules (28). Celletti et al found that adding strain elastosonography of Strain Ratio to K-TIRADS assessment can significantly increase its sensitivity and negative predictive value (30).…”
Section: Discussionmentioning
confidence: 99%
“…When the conventional B-mode image is properly adjusted and the CEUS mode activated, a microbubble contrast agent is injected as an intravenous bolus, generally with a dose of around 1.0-2.0 mL, followed by 5-10 mL of saline; however, specific amounts of CA and saline vary between operators and institutions [30][31][32][33]. A CEUS timer is started simultaneously with the injection of the contrast agent, and cine-clips of the scanning are stored digitally as raw data for 2-3 min before being processed, but the length of examination differs between sources and institutions, with most authors choosing a time period of at least 2 min [34,35]. Only one nodule can be evaluated for each injection of contrast agent.…”
Section: The Technique Of Contrast-enhanced Ultrasound In Thyroid Imagingmentioning
confidence: 99%
“…A similar study was carried out by Xu et al in which 432 thyroid nodules were analyzed with CEUS and six suspicious features were pointed out as being specific in differentiating benign from malignant nodules: slow wash-in (p = 0.001), slow time to peak (p = 0.002), non-uniform enhancement (p = 0.023), irregular enhancement (p = 0.002), unclear enhancement boundary (p = 0.012) and no visible ring enhancement (p = 0.004) [34]. As in other studies, CEUS combined with TI-RADS showed better accuracy than any of the two alone, achieving a sensitivity of 85.66% and specificity of 83.33% [49,67].…”
Section: Quantitative Analysis Of Thyroid Nodules In Ceusmentioning
confidence: 99%
“…In several previous studies, the conventional US features and CEUS characteristics were taken together to be analyzed. Some suspected US and CEUS characteristics may be excluded in multivariance analysis ( 25 , 26 ). But in clinical practice, being limited by technology or acceptance of patients, CEUS has not been extensively promoted at present.…”
Section: Discussionmentioning
confidence: 99%